Risk of Heart Failure With Preserved Ejection Fraction in Older Women After Contemporary Radiotherapy for Breast Cancer. Issue 15 (11th April 2017) - Saiki, Hirofumi; Petersen, Ivy A.; Scott, Christopher G.; Bailey, Kent R.; Dunlay, Shannon M.; Finley, Randi R.; Ruddy, Kathryn J.; Yan, Elizabeth; Redfield, Margaret M.
Abstract : Background: Cardiomyocytes are resistant to radiation. However, cardiac radiation exposure causes coronary microvascular endothelial inflammation, a perturbation implicated in the pathogenesis of heart failure (HF) and particularly HF with preserved ejection fraction (HFpEF). Radiotherapy for breast cancer results in variable cardiac radiation exposure and may increase the risk of HF. Methods: We conducted a population-based case-control study of incident HF in 170 female residents of Olmsted County, Minnesota (59 cases and 111 controls), who underwent contemporary (1998–2013) radiotherapy for breast cancer with computed tomography–assisted radiotherapy planning. Controls were matched to cases for age, tumor side, chemotherapy use, diabetes mellitus, and hypertension. Mean cardiac radiation dose (MCRD) in each patient was calculated from the patient's computed tomography images and radiotherapy plan. Results: Mean age at radiotherapy was 69±9 years. Of HF cases, 38 (64%) had EF≥50% (HFpEF), 18 (31%) had EF<50% (HF with reduced EF), and 3 (5%) did not have EF measured. The EF was ≥40% in 50 of the 56 HF cases (89%) with an EF measurement. The mean interval from radiotherapy to HF was 5.8±3.4 years. The odds of HF was higher in patients with a history of ischemic heart disease or atrial fibrillation. The MCRD was 2.5 Gy (range, 0.2–13.1 Gy) and higher in cases (3.3±2.7 Gy) than controls (2.1±2.0 Gy; P =0.004). The odds ratio (95% confidence interval) for HF per log MCRD was 9.1 (3.4–24.4) for any HF, 16.9 (3.9–73.7) for HFpEF, and 3.17 (0.8–13.0) for HF with reduced EF. The increased odds of any HF or HFpEF with increasing MCRD remained significant after adjustment for HF risk factors and in sensitivity analyses matching by cancer stage rather than tumor side. Only 18.6% of patients experienced new or recurrent ischemic events between radiotherapy and the onset of HF. Conclusions: The relative risk of HFpEF increases with increasing cardiac radiation exposure during contemporary conformal breast cancer radiotherapy. These data emphasize the importance of radiotherapy techniques that limit MCRD during breast cancer treatment. Moreover, these data provide further support for the importance of coronary microvascular compromise in the pathophysiology of HFpEF. Abstract : Supplemental Digital Content is available in the text.